Unified model for fully and partially FRP confined circular and square concrete columns subjected to axial compression. (15th January 2022) - Shayanfar, Javad; Barros, Joaquim A.; Rezazadeh, Mohammadali
Highlights: A new methodology for unification of confinement model for circular and square concrete columns with full/partial confining system is introduced. Consideration of non-uniform concrete lateral expansibility at the horizontal and vertical directions improves model predictive performance. A new methodology for reflecting the confinement path effect in confinement-induced improvements is proposed. Proposed analytical model demonstrated a good predictive performance. Abstract: Even though the usage of Fiber-reinforced polymer (FRP) full confinement arrangement is a more reliable and efficient strengthening technique than a partially confining strategy, it might not be cost-effective in real cases of strengthening. Experimental researches have demonstrated that confinement strengthening strategy is more effective for the case of circular columns compared to its application on square columns. This paper is dedicated to introducing a new unified model for determining the concrete confinement characteristics of FRP fully/partially confined circular/square concrete columns subjected to axial compressive loading. Through unification, the variations of the key parameters can be evaluated more-widely based on a unified mathematical framework. Consequently, it leads to the continuity in the predictions of FRP confinement-induced improvements for the different types of columns, contrary to those obtained from models only applicable to a specified cross-section or confining system. The substantial influence of non-homogenous concrete expansion distribution at the horizontal and vertical directions is taken into account in the determination of confinement pressure, besides arching action, by following the concept of confinement efficiency factor. Since the confinement-induced improvement is a function of its confining stress path, a new methodology is proposed to predict global axial stress–strain relation of FRP confined concrete columns considering confinement path effect, based on an extensive set of experimental results including 418 test specimens. The predictive performance of the developed model is assessed by simulating experimental tests reported in the literature.